"Do not harm the trees!" Ecology, Empire, and Translation in the Book of Revelation. Issue 3 (December 2019) - Perry, Peter S.
The book of Revelation shows an unexpected interest in trees, and not only for their symbolic or anthropocentric value. Relevance theory helps compare various interpretive options an audience might consider. An audience's understanding of the warning to "not harm the trees" will be affected by their awareness of the effects of storms, locust plagues, imperial deforestation, siege tactics, and prophetic use of these topics to expose the effects of human sin against creation. Paratextual aids in the translation of these passages will help modern audiences become more aware of these cognitive effects. Using different words to translate the Greek terms δένδρον (used to refer to earthly trees that other creatures are dependent on) and ξύλον (used for the symbolic "Tree" of Life) further emphasizes the earthly and ecological concern of the Seer's visions.